Complexos agroindustriais e ações na organização sócio-espacial: uma análise em geografia rural - Oliveira, Ana Leticia de (2011)
The research deals with the understanding of the behavior and manifestations of the agroindustrial complexes as developers of dynamic changes in colonial spatiality in which they operate. They influence the production process, changing and re-creating the productive matrix subjected to the action of the flows of capital which is installed on the current production system. The established relationships permeate the production chain especially by dealing with production of the raw material for the agro-industry, thus allowing knowledge on its behavior in order to achieve its size in the context of growth and socioeconomic progress of the local spatiality. The relevance of the study is to assess the activities of grazing livestock in the establishments and the existent relationships with the agribusiness, maintaining the meanings of horizontality and verticality, as well as to reveal the influence exerted on the definitions and economic, political, social organization of a given spatiality (in this sense, small municipalities such as Três Passos - RS. This study assumes significance considering that the agro-industrial complexes are present in the structure of economic and social spaces where they settle. For the development of the proposed research, the methodology used is the systemic understanding of a reality composed of complex relationships which highlight the Agroindustrial Complex Sadia S / A, and the categories of spatial analysis contrasted by rural and urban areas that form the investigated spatial Municipality. A critical analysis was also used, allowing the confront between some subsystems: political, economic and sociocultural as well as occasional technical and environmental changes in the way of life of people involved, directly and indirectly, with the dynamic processes that manifest the current organization of space. The presence of Agroindustrial Complex is identified in this research as an action of the capitalist dynamics. Its globalized reproduction process has promoted a profound socio-spatial interference on the old production system of colonial origin.